PERSEPSI SISWA TENTANG KEADAAN PSIKOLOGIS SENSE OF HUMOR GURU DENGAN MOTIVASI BELAJAR SISWA KELAS VII SMPN 3 BATUSANGKAR - Dwi Wahyuni (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2017)
This study is the students' perceptions about the teachers’ psychological sense of humor toward the learning motivation of grade VII SMPN 3 Batusangkar showed a positive relationship. There is a relationship between students' perceptions about the sense of humor with the learning motivation. This research is a correlation research that shows a positive relationship. The population of this study was the students of grade VII SMPN 3 Batusangkar which amounted to 214 people with the sample of the study amounted to 54 people taken with random sampling. The instrument in this research is questionnaire which Likert scale with four choices of answers consisting of: SS (Strongly agree, S (Agree), TS (Disagree), and STS (strongly disagree) The results of this study illustrates that there is a positive relationship of humor with the students motivation to learn who give a good impact in learning process with a pleasant situation and comfortable and not rigid so it can improve the spirit of student learning.